2014
DOI: 10.1080/1068316x.2014.989167
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and personal experiences of unwanted attention among Portuguese male students

Abstract: The present study investigated male perceptions and personal experiences of ‘unwanted attention’ (UA), as well as possible associations between perceptions and personal experiences of UA. Ninety-one male college students, from five Portuguese universities, were asked to indicate which of a continuum of 47 behaviours represented UA. Although UA, stalking and harassment are rarely addressed in Portugal, male college students shared a clear understanding of what behaviours constituted UA, with the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
0
16
0
10
Order By: Relevance
“…The research cited above compared perceptions on a range of variables, including the extent to which behavior constituted stalking and necessitated police intervention. Seven studies by Sheridan and colleagues (Björklund, Häkkänen-Nyholm, Roberts & Sheridan, 2010;Chiri, Sica, Roberts, & Sheridan, 2009;Jagessar & Sheridan, 2004;Pereira, Matos, Sheridan, & Scott, 2015;Sheridan, Davies & Boon 2001, Sheridan, Gillett, & Davies, 2000 have found that non-representative student and community samples of British men, Portuguese men, British women, Italian women, Finnish women and Trinidadian women hold similar perceptions regarding which of a list of intrusive behaviors are unacceptable. This finding supports the defensive attribution bias explanation of sex differences in judgments concerning stalking cases, in that when participants are asked to provide context-free judgments without details of a hypothetical perpetrator and target, sex differences are not identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research cited above compared perceptions on a range of variables, including the extent to which behavior constituted stalking and necessitated police intervention. Seven studies by Sheridan and colleagues (Björklund, Häkkänen-Nyholm, Roberts & Sheridan, 2010;Chiri, Sica, Roberts, & Sheridan, 2009;Jagessar & Sheridan, 2004;Pereira, Matos, Sheridan, & Scott, 2015;Sheridan, Davies & Boon 2001, Sheridan, Gillett, & Davies, 2000 have found that non-representative student and community samples of British men, Portuguese men, British women, Italian women, Finnish women and Trinidadian women hold similar perceptions regarding which of a list of intrusive behaviors are unacceptable. This finding supports the defensive attribution bias explanation of sex differences in judgments concerning stalking cases, in that when participants are asked to provide context-free judgments without details of a hypothetical perpetrator and target, sex differences are not identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, if these behaviors are performed repeatedly against another individual who views them as unwanted, they can be threatening [9][10][11]. Stalking has been defined in various ways, including strict legal definitions that require the stalker to demonstrate intent and the victim to feel fear, or by broader definitions that include lists of constituent behavior [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As Chapman and Spitzberg (2003) indicated, analyses based only on samples from individualist cultures cannot be generalized to collectivist cultures. Where differences did occur, they were between the collectivist cultures and the individualistic culture (Jagessar & Sheridan, 2004;Pereira et al, 2015). Analysis of samples from six sub-disciplines in psychology revealed that 96% of participants were from WEIRD countries (e.g., Australia, Europe, and the United States).…”
mentioning
confidence: 99%
“…The other principal method of examining perceptions of stalking and intrusive behavior involves respondents reading through a list of intrusive activities and indicating those they believe to constitute stalking, or consider to be unacceptable (see Chapman & Spitzberg, 2003;Jagessar & Sheridan, 2004;Lambert, Smith, Geistman, Cluse-Tolar, & Jiang, 2013;McKeon, McEwan, & Luebbers, 2015;Pereira, Matos, Sheridan, & Scott, 2015;Sheridan, Davies, & Boon, 2001;Sheridan, Gillett, & Davies, 2000;Sheridan, Gillett, & Davies, 2002;Yanowitz, 2006). These works were conducted in Australia, Japan, Portugal, Trinidad, the United Kingdom, and the United States.…”
mentioning
confidence: 99%
See 1 more Smart Citation